2013
DOI: 10.1111/pcmr.12171
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to vemurafenib resulting from a novel mutation in the BRAFV600E kinase domain

Abstract: Summary Resistance to the BRAF inhibitor vemurafenib poses a significant problem for the treatment of BRAFV600E-positive melanomas. It is therefore critical to prospectively identify all vemurafenib-resistance mechanisms prior to their emergence in the clinic. The vemurafenib-resistance mechanisms described to date do not result from secondary mutations within BRAFV600E. To search for possible mutations within BRAFV600E that can confer drug resistance, we developed a systematic experimental approach involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 24 publications
1
47
0
1
Order By: Relevance
“…Mirroring the clinical paradigm of acquired Vemurafenib (from now on indicated as PLX4032) resistance [42,43], we used the well characterized BRAF-mutated A375 metastatic cell line, and two independent isogenic metastatic melanoma cell models of acquired resistance (PLX4032-sensitive: 451-LU or M1617 and PLX4032-resistant: 451-LU/RES or M1617/RES [10]) to investigate modalities for overcoming or bypassing drug resistance. The resistance mechanism of 451-LU/RES and M1617/RES has been previously described and found to largely rely on a switch to the CRAF or ARAF isoforms resulting in MEK1 hyper-activation after PLX4032 treatment [10].…”
Section: Mek Inhibitor U0126 Sensitizes Plx4032-resistant Melanoma mentioning
confidence: 99%
“…Mirroring the clinical paradigm of acquired Vemurafenib (from now on indicated as PLX4032) resistance [42,43], we used the well characterized BRAF-mutated A375 metastatic cell line, and two independent isogenic metastatic melanoma cell models of acquired resistance (PLX4032-sensitive: 451-LU or M1617 and PLX4032-resistant: 451-LU/RES or M1617/RES [10]) to investigate modalities for overcoming or bypassing drug resistance. The resistance mechanism of 451-LU/RES and M1617/RES has been previously described and found to largely rely on a switch to the CRAF or ARAF isoforms resulting in MEK1 hyper-activation after PLX4032 treatment [10].…”
Section: Mek Inhibitor U0126 Sensitizes Plx4032-resistant Melanoma mentioning
confidence: 99%
“…Deep mutational scanning is a powerful tool for exploring the molecular basis of protein function (7,15,25,26). However, restrictions on functional assays have limited its general applicability, particularly for enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in enzyme sequence-function mapping has used in vivo assays that couple an enzyme's function to cellular growth (7,(24)(25)(26). These in vivo selections are limited not only in the types of enzyme functions that can be analyzed, but also by the range of experimental conditions compatible with the intracellular environment.…”
Section: Romero Et Almentioning
confidence: 99%
“…This study also quantified mutational rates and demonstrated that for different mutations (e.g., G/A or A/C) these rates spanned more than two orders of magnitude. Systematic analyses of engineered mutations have been extended beyond microbes to investigate drug resistance in mammalian cells (Wagenaar et al 2014). This study of the V600E BRAF oncogene systematically identified mutations in the kinase active site that enable cultured cells to grow in the presence of drug therapy.…”
Section: Concluding Thoughtsmentioning
confidence: 99%